(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Sales funnels and B2B processes are crucial to understanding the process of converting leads to customers. Organizations have used various approaches to enhance the management of their leads to become customers, ensuring a high conversion rate. This article evaluates predictive analytics and sales technology to advance sales funnels and B2B processes to cover incremental value in organizational marketing and development. Considerably, sales funnels and B2B processes begin at the awareness stage, followed by the customer’s developing interest. Then, the product’s benefits and pricing are considered before purchasing. This study proposes the use of Deep Neural networks (DNNs), Bidirectional Long Short-Term Memory (BiLSTM), and Light Gradient Boosting Machine (Light GBM) to assist in advancing the sales funnels and B2B processes. The article indicates that using DNN helps understand the influence of strategies and interactions, making the sales approach more concentrated on handling conversions. The use of BiLSTM works well with sequential data, offering insight into customer journeys and leading to an understanding of conversion probability and customer journeys. The application of Light GBM nonetheless indicates the possibility of handling lead scoring and customer segmentation to target marketing incentives. DNN, Light GBM, and BiLSTM work in a relevant manner to help develop sales funnels and B2B processes to optimize customer journeys and increase conversion rates.